2022
DOI: 10.1128/aem.02302-21
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Bacillus cereus Group Isolates' Resistance Using Disk Diffusion and Broth Microdilution and the Correlation between Antimicrobial Resistance Phenotypes and Genotypes

Abstract: Bacillus cereus group isolates (n = 85) were screened for phenotypic resistance to 18 antibiotics using broth microdilution and CLSI M45 Bacillus spp. breakpoints. The susceptibility to 9 out of 18 antibiotics was tested also using disk diffusion method and M100 Staphylococcus spp. breakpoints. Overall, a high prevalence of susceptibility to clinically relevant antibiotics was identified using broth microdilution. For most tested antibiotics, a poor c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 55 publications
3
6
0
Order By: Relevance
“…Four beta-lactamase genes were detected, in agreement with previous studies that found beta-lactamase genes as well as phenotypic resistance to be very common in the B. cereus group, including B. thuringiensis ( Luna et al., 2007 ; Park et al., 2009 ; Kim et al., 2015 ; Yim et al., 2015 ; Fiedler et al., 2019 ; Bianco et al., 2021 ; Mills et al., 2022 ). Even though a single vancomycin resistance gene was found, a vancomycin resistance seems unlikely, as individual van genes were previously reported in the B. cereus group but were insufficient to confer phenotypic resistance ( Arthur et al., 1992 ; Patel et al., 1997 ; Bianco et al., 2021 ; Mills et al., 2022 ). Genes associated with resistance to macrolide ( mhpL , abc-f ), lincosamide-streptogramin ( lsa ), streptogramin ( vat ), streptothricin ( sat A ), phenicol ( catA ) and fosfomycin ( fosB ) drug families were also detected in the three analyzed strains.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Four beta-lactamase genes were detected, in agreement with previous studies that found beta-lactamase genes as well as phenotypic resistance to be very common in the B. cereus group, including B. thuringiensis ( Luna et al., 2007 ; Park et al., 2009 ; Kim et al., 2015 ; Yim et al., 2015 ; Fiedler et al., 2019 ; Bianco et al., 2021 ; Mills et al., 2022 ). Even though a single vancomycin resistance gene was found, a vancomycin resistance seems unlikely, as individual van genes were previously reported in the B. cereus group but were insufficient to confer phenotypic resistance ( Arthur et al., 1992 ; Patel et al., 1997 ; Bianco et al., 2021 ; Mills et al., 2022 ). Genes associated with resistance to macrolide ( mhpL , abc-f ), lincosamide-streptogramin ( lsa ), streptogramin ( vat ), streptothricin ( sat A ), phenicol ( catA ) and fosfomycin ( fosB ) drug families were also detected in the three analyzed strains.…”
Section: Discussionsupporting
confidence: 90%
“…Thirteen chromosomally encoded AMR genes were predicted. Four beta-lactamase genes were detected, in agreement with previous studies that found beta-lactamase genes as well as phenotypic resistance to be very common in the B. cereus group, including B. thuringiensis (Luna et al, 2007;Park et al, 2009;Kim et al, 2015;Yim et al, 2015;Fiedler et al, 2019;Bianco et al, 2021;Mills et al, 2022). Even though a single vancomycin resistance gene was found, a vancomycin resistance seems unlikely, as individual van genes were previously reported in the B. cereus group but were insufficient to confer phenotypic resistance (Arthur et al, 1992;Patel et al, 1997;Bianco et al, 2021;Mills et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The broad diversity of Bacillus allows gene regulation that increases its pathogenicity (Bottone, 2010). Previous studies identified MDR phenotypes in this group (Torkar and Bedenic, 2018;Liu et al, 2018, Mills et al, 2022. Some MDR strains of Bacillus sp obtained in the present study cause food poisoning.…”
Section: Discussionmentioning
confidence: 58%
“…Since B. cereus group strains are clinically significant, determining their resistance/susceptibility toward antimicrobial agents is essential for treatment during disease outbreaks. Even though most infections caused by B. cereus group strains may get better without antimicrobial treatment, it is important to be vigilant as new B. cereus group infection strains may emerge in the future ( Mills et al, 2022 ). Based on the antibiotic susceptibility profiles, the B. cereus group isolates were further classified into four different groups (I, II, III, and IV) according to the MDR patterns ( Table 7 ).…”
Section: Resultsmentioning
confidence: 99%